A bedtime for Bear - Becker, Bonny; Denton, Kady MacDonald (Somerville, Mass. : Candlewick Press, 2010)
A small but effervescent overnight guest tries the patience of a curmudgeonly bear who needs absolute quiet to fall asleep.
Keywords: Bedtime -- Fiction; Sleepovers -- Fiction; Bears -- Fiction; Mice -- Fiction; Friendship -- Fiction; Bedtime -- Fiction; Sleepovers -- Fiction; Bears -- Fiction; Mice -- Fiction; Friendship -- Fiction